KEWAJIBAN PAJAK BAGI PELAKU JASA TITIPAN - Widjaja, MF Djeni Indrajati (Jurnal Serina Abdimas, 2023)
Jastip or entrusted services is a new business opportunity that is capitalized on technology, by using a smartphone, internet quota and relying on photo shots, a turnover of up to millions or even hundreds of millions of rupiah can be generated. Apart from not requiring large capital, this business opportunity is also easy to run even by a student. Jastip's activities have now been transformed from previously only social and cultural affairs into a profitable business opportunity. According to the tax perspective, Jastip's activities are divided into two, namely Direct Selling and Personal Shopper. Direct Selling is a direct selling method. The process of selling ordered goods entrusted by the buyer to the jastip seller by taking advantage of the difference between the purchase price and the selling price. Personal Shopper is the process of selling ordered goods that are entrusted by the buyer to the jastip seller by taking advantage of the fee agreed upon by both parties. In contrast to personal shoppers who shop according to the order of the customer, direct selling provides certain stocks of goods that are considered highly sought after/ hype for sale in the Indonesian market. The tax obligations of the jastip business are in the form of registering, calculating, depositing, and reporting taxes.